Embedding Abductive Inference in Defeasible Reasoning - Delrieux, Claudio (2002)
In this work we consider the problem of characterizing abductive inference in defeasible reasoning systems, in particular, in argumentative reasoning. We present an inference system based on an implicational segment of a relevant logic. Then we will discuss some issues arising the pragmatic acceptance of abductive inferences in nonmonotonic theories, in particular the accrual of explanations, and the strength of abductive inferences using defeasible rules, and the combination of diferent kind of defeaters. Finally, we show how our system can accommodate anomalous observations and characterize all the possible outcomes that a nonmonotonic theory may face when confronted with new evidence.